2014
DOI: 10.1007/s13318-014-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of rosuvastatin in males and females

Abstract: Rosuvastatin is used to treat dyslipidemia and is metabolized by CYP2C9 that shows variable metabolic activity in males and females. Pharmacokinetics (PK) of drugs varies in males and females that may result in altered drug response and therapeutic efficacy. In current study, PK of rosuvastatin has been evaluated in males and females. A single oral dose (40 mg rosuvastatin), open-label and non-controlled PK study was arranged. A reversed phase HPLC method was applied for quantification of rosuvastatin in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
10
2
Order By: Relevance
“…15 However, in our studies, no statistical differences of pharmacokinetic characteristics were found between Chinese male and female subjects. 15 However, in our studies, no statistical differences of pharmacokinetic characteristics were found between Chinese male and female subjects.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…15 However, in our studies, no statistical differences of pharmacokinetic characteristics were found between Chinese male and female subjects. 15 However, in our studies, no statistical differences of pharmacokinetic characteristics were found between Chinese male and female subjects.…”
Section: Discussioncontrasting
confidence: 70%
“…Additionally, Nazir et al evaluated gender-based pharmacokinetics differences in Asian subjects (Pakistani) and found the C max and AUC 0-t values of rosuvastatin are significantly higher in women. 15 However, in our studies, no statistical differences of pharmacokinetic characteristics were found between Chinese male and female subjects. A clear food effect was observed in male and female groups as well.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…61 Higher systemic exposure of statins in women was observed for pitavastatin, 78 while there is no gender difference in systemic exposure of pravastatin. 79 For rosuvastatin, one study reported higher AUC and C max in women than in men, 80 while no gender difference was observed for rosuvastatin pharmacokinetics in another study. 81 The gender difference in pharmacokinetics of CQ and the effects of CQ on pharmacokinetics of statins have not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…High-fat and high-calorie meals resulted in a reduction of rosuvastatin exposure and a decrease in absorption rate of rosuvastatin ( Chen et al, 2020 ), showing the relevance of diet. Sex ( Nazir et al, 2015 ) and drug formulation ( Balakumar et al, 2013 ; Dudhipala and Veerabrahma, 2017 ) are other listed factors that influence pharmacokinetics and/or response to rosuvastatin.…”
Section: Introductionmentioning
confidence: 99%